Dealing with office fires - Safetycare Australia Pty. Ltd. ([S.l.] : Safetycare Australia, 1995)
Disscussion on planning the office layout, established office safety procedures, training in fire prevention, identification and control
Accompanied by 1 trainer's manual
Keywords: Fire prevention; Fire prevention -- Equipment and supplies